An Enterprise Architecture approach for Data Quality management within Namibian Health Information Systems - Katjimune, Vitjitua (Department of Information Systems, 2025)
A Health information system (HIS) is regarded a key pillar in any healthcare sector. Yet, for many developing countries, challenges with data quality management have affected the adequate use of HIS. Resilient and well-functioning HIS systems contribute to the delivery of high-quality healthcare services, enhanced operational efficiency, informed decisionmaking, and the advancement of public health systems. Efforts to improve the quality of data in HIS has recently been a research interest in healthcare literature. This study investigates the use of Enterprise Architecture (EA) principles as an approach to data quality management in the context of Namibian Health Information Systems (NHIS). The study focuses on the principles outlined in The Open Group Architectural Framework (TOGAF) EA framework. This study followed a Grounded Theory Methodology (GTM). The themes from literature and data were used to form a conceptual model. Themes that emerged from the data include governing laws, standardization, data quality assessment and data quality assurance. The findings highlight the use of EA principles in Namibian HIS (NHIS) and showed that the standard out-of-the-box implementation of EA may not be suitable for use within a healthcare setting. The results, however, indicate that EA implementation should be informed by healthcare laws and policies particularly those pertaining to patient privacy. Furthermore, data quality challenges and some of the contextual conditions were discussed in depth and found to be similar to the findings in literature.